TECHNOLOGIES AND DEVELOPMENTS FOR HYDROGEN PRODUCTION (REVIEW) - Simeiko, Kostyantyn; Trofimov, Ihor; Zagrebelnyi, Oleksiy; Shulga, Oleg; Kozhan, Oleksiy (Science-based technologies, 2023)
The article considers the issues of modern technologies for hydrogen production and development of technologies for its production. The main purpose of the work was the analysis of industrial technologies and scientific research aimed at obtaining hydrogen to determine the most optimal ways to produce it. The article describes technological processes, main advantages and disadvantages of technologies and developments for the production of hydrogen and hydrogen-containing gas. The article also considers the needs of hydrogen use by both industry and the population. Due to the fact that the combustion of hydrogen produces water, it is an energy-efficient and environmentally friendly energy carrier. Also, hydrogen is used in many industries, namely: in chemical synthesis, oil refining, heat treatment of metals, in the production of vegetable oils, glass industry, in cooling systems in energy, transport and other industries. The choice of the most cost-effective and environmentally friendly method of hydrogen production will further develop its wider use in energy, transport and metallurgy to replace technologies with high carbon dioxide emissions. The main industrial process for the production of hydrogen and hydrogen-containing gases is steam catalytic conversion of hydrocarbons (natural gas, gas condensate, light oil fractions). According to the authors, the following seven alternatives to hydrogen production may have the potential for industrial implementation: high-temperature pyrolysis of natural gas, pyrolysis and gasification of biomass, fermentation of biomass flows into biogas combined with biogas conversion, thermochemical splitting of water, photocatalysis (using photoelectrochemical cells (PECs), supercritical gasification of water by biomass, electrolysis using excess electricity.The research results can be applied in the energy industry, the transport industry, in particular in the operation of spacecraft. The results of the article can be applied in practice by power engineers, expert chemmotologists, as well as scientists involved in the development of new technologies for hydrogen production.